Numerical analysis on spatial universality of similarity technique inside molten salt reactor system. (January 2018) - Seo, Seok Bin; Shin, Yukyung; Bang, In Cheol
Highlights: The feasibility of using simulant fluid for various MSR systems are numerically tested based on the similarity technique. The spatial consistency between global characteristics and local characteristics evaluated from the similarity techniques is tested. It is found that the local characteristics of molten salt evaluated by the similarity technique can well reproduce the global thermal-hydraulics of molten salt in existing MSR systems. Abstract: To compensate the difficulties in the study on a thermal-hydraulic system in a full scale, a similarity technique has been developed to predict the thermal characteristics of fluid in the full-scale system under smaller and simpler conditions. Then the feasibility of using simulant fluid for various MSR systems are numerically tested based on the similarity technique in this study. The utilization of thermal-hydraulic code with the simulant fluid, DOWTHERM RP, reproduces the system design values and the Nusselt numbers for the representative MSR systems including MSFR, MOSART, and MSBR. The steady state results confirm the applicability of similarity technique using DOWTHERM RP to simulate the thermal-hydraulic phenomena in MSR systems. The evaluated Nusselt numbers from the analysis results well agrees with the theoretical Nusselt numbers for all the MSR systems. Thus, it is concluded that the numerical analysis using the similarity technique well reproduces the steady-state heat transfer performance of the molten salts regardless of system configuration and specifications. In addition, the spatial consistency between global characteristics and local characteristics evaluated from the similarity techniques is tested. From the transient analyses results under the loss of flow accident, it is found that the local characteristics of molten salt evaluated by the similarity technique can well reproduce the global thermal-hydraulics of molten salt in existing MSR systems.